STRATEGI MENINGKATKAN MUTU PENDIDIKAN MELALUI MANAJEMEN SARANA DAN PRASARANA PADA SMK NEGERI 1 SINGKAWANG - Mellky Yulius (Khazanah Pendidikan, 2020)
ABSTRACTThe school is a social institution whose existence is part of the nation's social system which aimsto produce capable, democratic, responsible, faithful, faithful, physically and spiritually healthyindividuals, possessing knowledge and skills, having a steady and independent personality. Inorder to achieve these objectives a strong curriculum is needed, both infrastructure andsuperstructure. The research aims to reveal strategies to improve the quality of education throughthe management of facilities and infrastructure in Singkawang 1 Vocational High School (SMK)with a focus on: 1). Facilities and infrastructure planning in Singkawang State Vocational School1, 2). Utilization of facilities and infrastructure in State Vocational School 1 Singkawang, 3).Monitoring of Facilities and Infrastructure at SMK Negeri 1 Singkawang, 4). Reporting onfacilities and infrastructure at SMK Negeri 1 Singkawang, 5). Obstacles encountered in facilitiesand infrastructure at SMK Negeri 1 Singkawang. The research method used is descriptiveresearch with a qualitative approach. Data validity is done by data triangulation, technicaltriagulation and member checking. Then the interactive data analysis with data reduction, datapresentation, conclusion or verification. The results showed that: 1). facility and infrastructureprogram planning has been made by the student department to develop facilities in schoolactivities. 2). The use of facilities and infrastructure is implemented in accordance with thelearning needs of each teacher and regulated and monitored in an orderly manner, 3).Supervision of facilities and infrastructure has been done directly by the school principal, 4).Reporting has been carried out regularly by the vice-principal on student affairs to the principal,5). Constraints faced in facilities and infrastructure are financing both for procurement andmaintenance. Based on the results of the study suggested the following things: 1) The principalis expected to optimize supervision of all activities that have been planned so that the specifiedgoals can be achieved. 2) Need to involve the community in the procurement of financing andmaintenance of facilities and infrastructure. 3) Teachers, administration is expected to beinvolved in the management of facilities and infrastructure.Keywords: Strategy, Education Quality, Management of Facilities and Infrastructure.